PENGARUH RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PERBANKAN ( Study pada Perusahaan Perbankan periode 2014-2017 yang Terdaftar di Bursa Efek Indonesia) - Mukhlis, Muhamad (Magister Manajemen Universitas Wisnuwardhana, 2019)
Abstract. This research aims to determine the effect of Return on Assets (ROA) and Return on Equity (ROE) simultaneously on the stock price of banking companies; to determine the effect of Return on Assets (ROA) and Return on Equity (ROE) partially on the stock price of companies, and; to determine which variable that is dominant between Return on Assets (ROA) and Return on Equity (ROE) on the stock price of companies. This research is explanatory research that aims to analyze the relationship between variable and other variables. The analysis technique used is descriptive test and hypothesis testing. Based on the results and the discussion in this research, it can be concluded as follows: 1) simultaneously or jointly between ROA and ROE affect the stock price of banking companies on the Indonesia Stock Exchange (IDX) in 2014-2017; 2) Partially Return on Assets (ROA) significantly influence the stock price of banking companies on stock price on the Indonesia Stock Exchange (IDX) in 2014-2017 while Return on Equity (ROE) has no significant effect on the stock price of banking companies on stock price on the Indonesia Stock Exchange (IDX) in 2014-2017. Analysis result dominant test indicates that Return on Assets (ROA) has a dominant influence on stock price compared to Return on Equity (ROE) Keywords: Return on Assets, Return on Equity, Share Prices